2012
DOI: 10.7314/apjcp.2012.13.2.637
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive Epidemiology of Primary Brain and CNS Tumors in Delhi, 2003-2007

Abstract: Asian Pacific J Cancer Prev, 13, 637-640 IntroductionBrain tumors though not frequent, contribute significantly to morbidity because of their relatively poor survival rate. A number studies from Western countries has reported on the pattern, incidence and mortality of brain and central nervous system (CNS) tumors. But no population based data have hitherto been reported on the descriptive epidemiology of brain and CNS tumors from India. So an attempt has been made to present the descriptive analysis of maligna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 2 publications
1
22
0
Order By: Relevance
“…The most prevalent forms of tumor, in our study, were: Astrocytoma (36.9%), GBM (24.8%) and Meningioma (16.3%). In the study reported by Manoharan et al (2012) the most frequently tumor types were gliomas (25.4%), glioblastomas (21.5%) and astrocytomas (20.6%), that was similar to our study, despite, they didn't studied the benign tumors prevalence such as meningioma. In a systematic review by Jazayeri et al (2013) the most common forms of tumor were Astrocytoma and Glioblastoma multiform (15.2% and 13.8%, respectively).…”
Section: Discussionsupporting
confidence: 91%
“…The most prevalent forms of tumor, in our study, were: Astrocytoma (36.9%), GBM (24.8%) and Meningioma (16.3%). In the study reported by Manoharan et al (2012) the most frequently tumor types were gliomas (25.4%), glioblastomas (21.5%) and astrocytomas (20.6%), that was similar to our study, despite, they didn't studied the benign tumors prevalence such as meningioma. In a systematic review by Jazayeri et al (2013) the most common forms of tumor were Astrocytoma and Glioblastoma multiform (15.2% and 13.8%, respectively).…”
Section: Discussionsupporting
confidence: 91%
“…In the population covered by our hospital cancer registry, the age adjusted incidence rates of brain and CNS tumors are low compared to the AAR of other registries of India (Manoharan et al, 2012). Literature suggests the prevalence of malignant brain tumors to be around 1-2% of adult cancers (Wrensch et al, 2002;Mckinney, 2004).…”
Section: Discussionmentioning
confidence: 80%
“…The ASR for glial tumours overall was reported about 11.9 per 100.000 person per year (Crocetti et al, 2012). In western Country the ASR was 3.9 for male and 2.4 for female per 100.00 (Manoharan et al, 2012).…”
Section: Discussionmentioning
confidence: 97%